2023
DOI: 10.1371/journal.pone.0292284
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between political instability and stock market performance: An analysis of the MSCI index in the case of Pakistan

Zhiying Mai,
Hassan Mujtaba Nawaz Saleem,
Muhammad Kamran

Abstract: The stock market is the barometer of the economy that reflects the overall health and direction of the economic development and is affected by different factors including social, environmental and political. It is important to investigate the effect of the political instability on the stock market performance, especially on emerging economies. Therefore, we aim to study the relationship between political instability and stock market performance in Pakistan. To meet our objectives, we used past data from 1996 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The study on Pakistan found that political stability has significant positive impact on the stock market performance while, political instability has negative impact on stock market performance. Moreover, other governance indicators have a significant positive impact on performance (Mai et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study on Pakistan found that political stability has significant positive impact on the stock market performance while, political instability has negative impact on stock market performance. Moreover, other governance indicators have a significant positive impact on performance (Mai et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%